Ethical Challenges of Parenting Interventions in Low- to Middle-Income Countries. (January 2018) - Morelli, Gilda; Quinn, Naomi; Chaudhary, Nandita; Vicedo, Marga; Rosabal-Coto, Mariano; Keller, Heidi; Murray, Marjorie; Gottlieb, Alma; Scheidecker, Gabriel; Takada, Akira
This article explores ethical issues raised by parenting interventions implemented in communities in low- to middle-income countries (LMICs) with rural, subsistence lifestyles. Many of these interventions foster "positive parenting practices" to improve children's chances of fulfilling their developmental potential. The practices are derived from attachment theory and presented as the universal standard of good care. But attachment-based parenting is typical primarily of people living Western lifestyles and runs counter to the different ways many people with other lifestyles care for their children given what they want for them. Thus, such parenting interventions involve encouraging caregivers to change their practices and views, usually with little understanding of how such changes affect child, family, and community. This undermines researchers' and practitioners' ability to honor promises to uphold ethic codes of respect and beneficence. Support for this claim is provided by comparing positive parenting practices advocated by the United Nations International Children's Emergency Fund (UNICEF; with the world health organization [WHO]) Care for Child Development (CCD) intervention with parenting practices typical of communities with rural, subsistence lifestyles—the most common of lifestyles worldwide and largely observed in LMICs. As UNICEF has a considerable presence in these countries, the CCD intervention was selected as a case study. In addition, parenting interventions typically target people who are poor, and the issues this raises regarding ethics of fairness and justice are considered. Recommendations are made for ways change agents can be sensitive to the living conditions and worldviews of communities, and, thus, be appropriately effective and ethically sensitive to the diverse needs of different communities.